Export and Import - Romi Alhadid Rangkuti; Putri Nandita; Dara Citra Pratiwi; Yuliana Saputri; Suhairi Suhairi (International Journal Labs, 2022)
The purpose of this study is to analyze the effect of exports and imports on economic growth in Indonesia in the long term and short term. The data used in this study is secondary data obtained from the World Bank 2000-2016. The analysis used is regression analysis using Error Corection Model (ECM) Method. Tests used in the model are Stationarity Test, R-Square Test, F Test and T Test. The result of this research is that long term, export variable and exchange rate influence to economic growth while import does not have an effect on to economic growth. In the short run, export and import variables affect economic growth, while exchange rates have no effect on economic growth.